Noninvasive Assessment of the Effect of Position and Exercise on Pulse Arrival to Peripheral Vascular Beds in Healthy Volunteers - Obata, Yurie; Ong, Qi Jia; Magruder, J. Trent; Grichkevitch, Helen; Berkowitz, Dan E.; Nyhan, Daniel; Steppan, Jochen; Barodka, Viachaslau (Frontiers in Physiology, 2017)
Background: The effects of position and exercise on pulse wave distribution across a healthy, compliant arterial tree are not fully understood. We studied the effects of exercise and position on the pattern of pulse arrival times (PATs) in healthy volunteers. Moreover we compared the pulse arrival time ratios to the respective distance ratios between different locations. Methods: Thirteen young healthy volunteers were studied, using an electrocardiogram and plethysmograph to simultaneously record pulse wave arrival at the ear lobe, index finger and big toe. We compared the differences in PAT between each location at rest and post-exercise in the supine, sitting, and standing position. We also compared the PAT ratio (toe/ear, toe/finger and finger/ear) to the corresponding pulse path distance ratios. Results: PAT was shortest at the ear then finger and longest at the toe regardless of position or exercise status. PATs were shorter post exercise compared to rest. When transitioning from a standing to sitting or supine position, PAT to the ear decreased, while the PAT to the toe increased, and PAT to the finger didn’t significantly change. PAT ratios were significantly smaller than predicted by the path distance ratios regardless of position or exercise status. Conclusions: Exercise makes PATs shorter. Standing position decrease PAT to the toe and increase to the ear. We conclude that PAT and PAT ratio represent the arterial vascular tree properties as surely as pulse transit time and pulse wave velocity.